If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 5 = 15 + 3x Reorder the terms: 5 + 8x = 15 + 3x Solving 5 + 8x = 15 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 5 + 8x + -3x = 15 + 3x + -3x Combine like terms: 8x + -3x = 5x 5 + 5x = 15 + 3x + -3x Combine like terms: 3x + -3x = 0 5 + 5x = 15 + 0 5 + 5x = 15 Add '-5' to each side of the equation. 5 + -5 + 5x = 15 + -5 Combine like terms: 5 + -5 = 0 0 + 5x = 15 + -5 5x = 15 + -5 Combine like terms: 15 + -5 = 10 5x = 10 Divide each side by '5'. x = 2 Simplifying x = 2
| 7x^2+12y^2= | | 7x+9=39+2x | | 7x+9=39+2z | | -3.6x-6.9-8x=-5.5 | | (9y+18)+(5x+x)=90 | | 9(4w-8)=12(3w+5) | | 2(3x-4)-12=(5x-3) | | 9y+18+5x+x=90 | | 9x+5+3x+1=90 | | Y=a+bx+cx^2+dx^3 | | 8x+6y=450 | | 2x+14=20-4x | | -30=5y-5 | | 8x+16=106-2x | | 21-7x=39-10x | | (4w+3)*2w=9w | | -17m-11=-9m-59 | | 7x+9=29-3x | | 3x+8=38-2x | | x-2+3=12 | | 3(2x+1)-4(x-2)=25 | | f(x)=-3x^2+15 | | 5*5+7-3= | | 110=w(w+15) | | W^2+15w=110 | | 4xy-4xz= | | t^2-3t=-2 | | 2=16-2p | | 12y^2+y-20=0 | | 1.5x+14=26+0.5x | | 5x+18=12x+4 | | 7w-3(4w+8w)=11 |